A Retrospective Study of Multi‐agent Chemotherapy including either Cyclophosphamide or Lomustine as Initial Therapy for Canine High‐grade T‐cell Lymphoma (2011‐2017). Issue 9 (22nd July 2019) - Elliott, J; Baines, S
Abstract : Multi‐agent chemotherapy (vincristine, epirubicin and prednisolone) including either cyclophosphamide (CEOP) or lomustine (LEOP) was given as first‐line chemotherapy to treatment‐naïve canine lymphoma patients with measurable, high grade T‐cell lymphoma (HGTCL). All patients responded to either CEOP or LEOP. Toxicity was typical of multi‐agent chemotherapy protocols and 25% of dogs receiving lomustine exhibited mild‐to‐moderate ALT elevation and 29% grade 3 or 4 neutropenia. Median progression‐free survival (100 versus 269 days) and overall survival (155 versus 327 days) were significantly higher in patients receiving LEOP compared to CEOP. Overall survival was improved for patients receiving LEOP compared to those receiving CEOP followed by lomustine‐based rescue therapy. The results of this retrospective study support further evaluation of lomustine as part of first‐line, multi‐agent therapy for patients with HGTCL.